A founder mutation MLC1 c.736delA associated with megalencephalic leukoencephalopathy with subcortical cysts‐1 in north Indian kindred. Issue 2 (18th April 2018) - Vellarikkal, S.K.; Jayarajan, R.; Verma, A.; Ravi, R.; Senthilvel, V.; Kumar, A.; Saini, L.; Gulati, S.; Lal, M.; Mathur, A.; Chhetri, M.K.; Faruq, M.; et al.
Abstract :